(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
Acetic acid (AA) poisoning is a serious health problem, especially in countries with a high level of availability of the substance. Acetic acid is used for domestic and industrial purposes, making it a common substance for accidental or intentional poisoning. In Uzbekistan, as in other Central Asian countries, acetic acid poisoning remains an urgent problem for the health care system, including primary care.